Agrarian movements and rural populism in Indonesia. (2nd August 2022) - White, Ben; Graham, Colum; Savitri, Laksmi
Abstract: In this article, we reflect on the changing trajectories of agrarian movements in Indonesia. In the two decades after independence, a left‐populist alliance of peasants, plantation workers, and other affiliate organizations achieved a mass following and were embraced by President Sukarno. In the aftermath of their violent destruction, the Suharto regime reordered agrarian movements into a single corporatist model. Suharto's downfall opened the way for the re‐emergence of agrarian organizations and movements. But two decades later, they remain small and fragmented, with little influence at the national level. In the changing conditions of rural life, and the increasingly authoritarian political context, progressive rural movements face dilemmas on questions both of their focus and goals and of tactical alliances with other progressive movements and political elites. A broader, more inclusive progressive populist alliance is a possibility, but with the continuing danger of co‐optation by forces of the populist right.